Sepsis-Induced Cardiomyopathy: Mechanisms and Treatments - Liu, Yan-Cun; Yu, Mu-Ming; Shou, Song-Tao; Chai, Yan-Fen (Frontiers in Immunology, 2017)
Sepsis is a lethal syndrome with a high incidence and a weighty economy burden. The pathophysiology of sepsis includes inflammation, immune dysfunction and dysfunction of coagulation, while sepsis-induced cardiomyopathy (SIC), defined as a global but reversible dysfunction of both sides of the heart induced by sepsis, plays a significant role in all of the aspects above in the pathogenesis of sepsis. The complex pathogenesis of SIC involves a combination of dysregulation of inflammatory mediators, mitochondrial dysfunction, oxidative stress, disorder of calcium regulation, autonomic nervous system dysregulation, and endothelial dysfunction. The treatments for SIC include the signal pathway intervention, Chinese traditional medicine, and other specific therapy. Here we reviewed the latest literatures on the mechanisms and treatments of SIC and hope to provide further insights to researchers and create a new road for the therapy of sepsis.